The Impact of Training and Development on Innovative Work Behavior: Exploring the Mediating Role of Knowledge Sharing - Kusumastuti, Yuliana Saridewi; Atthahira, Nadia Ashmi; Purba, Mambang Purwanto (Universitas Mohammad Husni Thamrin, 2025)
In today's highly competitive and rapidly evolving business environment, building innovative work behavior (IWB) among employees is crucial to ensuring organizational success and sustainability. This study aims to analyze the effect of training and development on innovative work behavior, with knowledge sharing as a mediating variable. The approach used was quantitative with a causality method. The sampling technique used was convenience sampling. The population in this study consisted of 1,036 employees of the Social Security Administration Agency (BPJS Ketenagakerjaan). A total of 278 respondents were selected based on certain criteria. Data analysis was conducted using Structural Equation Modeling (SEM) with the assistance of AMOS software. The results showed that training and development had a positive and significant effect on innovative work behavior and knowledge sharing practices among employees. Furthermore, knowledge sharing was proven to significantly mediate the relationship between training and development and innovative work behavior. These findings emphasize the importance of both factors in building an innovative culture within an organization. This study provides theoretical and practical contributions, particularly for institutions such as BPJS Ketenagakerjaan. Emphasis is placed on the importance of designing training and development programs that not only enhance technical capabilities, but also encourage psychological empowerment and knowledge sharing practices, which will ultimately lead to increased innovative work behavior and overall organizational performance.